Hybrid RF And Solar PV Energy Harvester - Saiful, Erva Natasha Mohd (Universiti Sains Malaysia, 2017)
Energy harvesting has been around for a very long time. At that time, energy was harvested in the early days of the electrical revolution by putting generators on river mills that were powered by running water to generate electricity. The most common energy is solar energy which is most important item in energy harvesting. The concept of energy extraction from nature, which can be used to replace the conventional power source. The energy harvester needs to be convert to voltage or current to power the system. One of the ways to use energy harvesting by using the hybrid sources. Hybrid sources can be formed by using three types of sources which are Thermoelectric Generator(TEG) that the variance of temperature between the surrounding and the heat. Secondly, the vibration sources that are used the vibration sources such as motor and the shaking device, the Radio Frequency(RF) that are produced radiated power. Other than that, energy harvesting is the first real-world implementation of scalable battery-less stand-alone wireless sensor platforms for quality of life and the Internet of Things (IoT) application. The energy that commonly used are solar energy technologies. However, the devices currently need to use electricity frequently but solar energy have it limitations. This thesis concerns on the investigation on harvesting energy for RF energy by using the solar panel. Both energy which are RF energy and solar energy can get from the solar panel. In the other words, the solar panel also act as the antenna for receiving the signal and convert to RF energy. The analysis will be made to analyze whether the RF energy can be got from solar panel. The patch antenna was designed and fabricated. The solar panel was tested with RF equipment to measure the solar panel performance parameters and compared with patch antenna. For the signal strength solar panel showed a good performance compared to patch antenna which for solar panel was -32.67dBm at 2.5GHz while patch antenna was -38.88dB at 2GHz. On the other hand, the ambient energy showed slightly difference in terms of receiving power but for the frequency, the frequency received was in range ±1.8GHz. Moreover, the gain for solar panel was 2.31dB and it was lower than patch antenna gains of 4.73dB due to the tolerance in PCB manufacturing process. In conclusion, the dominant frequency for solar panel is ±1.8GHz which the application for this frequency is in GSM.